Pengaruh Penerapan Model Pembelajaran Paired Storytelling Terhadap Kemampuan Berbicara Siswa Kelas IV SD Negeri 1 Kadipiro Kabupaten Bantul - Siti Mutia Syahroh; Akbar Al Masjid (Universitas Sarjanawiyata Tamansiswa, 2023)
This research is a quantitative research with an experimental type that aims to describe: 1) the extent of students' speaking skills in class IV SD Negeri 1 Kadipiro using the PST learning model. 2) the extent to which students' speaking skills in class IV SD Negeri 1 Kadipiro use the NHT learning model. 3) differences in the speaking ability of fourth grade students at SD Negeri 1 Kadipiro between using the PST learning model and the NHT learning model. Data collection techniques using tests in the form of performance for the pretest and posttest. Data analysis techniques used descriptive analysis, equivalence test, normality and homogeneity test and hypothesis testing. The results of this study showed that descriptively the speaking skills of the experimental group students using the PST learning model obtained an average of 84.68 which was included in the high category, while the speaking skills of the control group students using the NHT learning model obtained an average of 78.36 which included in the high category. Comparatively there are differences in the speaking skills of the experimental class students using the PST learning model and the control class students using the NHT learning model seen from the different average scores. Learning using the PST learning model is higher than the NHT learning model